Physics in architecture projects, a perfect match on Alamillo’s bridge by Santiago Calatrava (2021)
The Alamillo’s bridge by Santiago Calatrava was studied, who develops projects and structures with morphological, sculptural, and conceptual aspects associated with physics and contemporary architecture, through experimentation with forms of nature, the movement of the human body and, materials such as steel and reinforced concrete. The methodological framework corresponded to a documentary study that determined the importance of the bridge from its historical context as part of the infrastructure of the 1992 Universal Exposition in Seville, as well as the analysis of the physical concepts used in its design and construction; and, a quantitativedescriptive study applied to the seventh semester students of the Architecture program of the Universidad Francisco de Paula Santander, Colombia, which determined their level of recognition of the physical concepts of this project. As a finding, it is highlighted that this bridge applied physical concepts such as: aerodynamics, torsion, compression, tension, traction, and gravitation, in compliance with its formal-aesthetic design criteria, and those students recognize the physical concepts, design and technical characteristics -formal, typical of the project. Likewise, it was determined that this urban landmark represents a comprehensive solution that solves the structure and form through solutions associated with the field of engineering, architecture, and physics.